Exploring the Gamelan Harmony Website for Elementary School Students - I Nyoman Jampel; Luh Nik Armini; Kade Sathya Gita Rismawan (International Journal of Elementary Education, 2025)
Students' psychological well-being is a critical factor in supporting academic success. However, academic stress among elementary school students especially those in upper grades—is increasing, with few integrated interventions tailored to their emotional needs. This study aims to design and develop the Gamelan Harmony website, an artificial intelligence (AI)-based platform integrated with Balinese gamelan music, as an innovative medium to support student relaxation and reduce learning-related stress. This research adopts a Research and Development (R&D) approach using a simplified Borg and Gall development model, focusing on the initial product design phase. Data were collected through observation, interviews, and questionnaires involving 2 language experts, 2 content experts, 2 media experts, 1 teacher, and 9 students for individual and small group trials. Data were analyzed using descriptive quantitative methods. Expert validation results showed that Gamelan Harmony achieved a “very valid” rating, with average scores above 95%. Practicality tests also yielded “very practical” results, with scores ranging from 90% to 96%. These findings suggest that integrating AI with local cultural elements has the potential to offer an educational, adaptive, and contextually relevant solution for managing stress among elementary school students.